2015
DOI: 10.3389/fonc.2015.00059
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Cognitive Impairment and Decline Associated with Adjuvant Chemotherapy in Women with Breast Cancer

Abstract: A meta-analysis was performed to quantify the magnitude and nature of the association between adjuvant chemotherapy and performance on a range of cognitive domains among breast cancer patients. A total of 27 studies (14 cross-sectional, 8 both cross-sectional and prospective, and 5 prospective) were included in the analyses, involving 1562 breast cancer patients who had undergone adjuvant chemotherapy and 2799 controls that included breast cancer patients who did not receive adjuvant chemotherapy. A total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 48 publications
11
83
0
19
Order By: Relevance
“…While CTX is associated with decreases in cognitive function, 44,61,69 the relationship between pain and cognitive function has not been evaluated in patients on CTX. AFI scores for patients in our study were slightly lower than scores of patients at the initiation of RT 60 or prior to breast cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While CTX is associated with decreases in cognitive function, 44,61,69 the relationship between pain and cognitive function has not been evaluated in patients on CTX. AFI scores for patients in our study were slightly lower than scores of patients at the initiation of RT 60 or prior to breast cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive assessment of spatial cognitive ability was not performed in previous studies. In addition, confounders such as chemotherapy were excluded, even if the magnitude of the impact of chemotherapy is still controversial [17,37]. In a meta-analysis of 17 studies on chemotherapy-induced cognitive impairment in patients with breast cancer, Jim et al [38] reported an impairment of verbal and visuospatial ability compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…This involves the risk that potential differences remain undetected. Generally, a differentiation between patients receiving chemotherapy and endocrine therapy is essential, because chemotherapy is a potential confounder [37,38]. Different types of endocrine therapy - anti-estrogens and AIs - should be studied separately.…”
Section: Discussionmentioning
confidence: 99%
“…Dowodzą temu liczne metaanalizy opierające się na wynikach badań tej grupy pacjentek [17][18][19][20][21].…”
Section: Chemobrain a Szpiczak Mnogiunclassified